INFLUENCE OF MAIN GEAR RATIO ON CAR FUEL EFFICIENCY IN THE DRIVE CYCLE - S. A. Gorozhankin; N. V. Savenkov; V. V. Ponyakin (Вестник СибАДИ, 2018)
Introduction. The article presents the improvement efficiency of fuel and economic properties of the vehicle in WLTC driving cycle by means of the main gear ratio changing. Materials and methods. Great attention is paid to the fuel consumption determination by the numerical simulation of the moving process in the driving cycle. To illustrate this process, a continuous function of the vehicle speed and various mathematical models of the internal combustion engine characteristics – based on the classical theory, and also on the basis of experimental studies with additional account of transient modes – is formed in the research. Results. Therefore, the corresponding values of the mass fuel consumption and the gear shifting algorithm are proposed in the article. Discussion. The obtained results allow to carry out the effect of individual gear ratios’ evaluation on the fuel and economic efficiency of the vehicle in the prospective World Harmonized Driving Cycle with additional consideration of the traction and speed performance changing. Сonclusion. It can be concluded that the calculation methods used in the research could be applied for solving the problems of complex optimization synthesis of structural and regime parameters in mechanical transmissions of modern automobiles.